177 Updated safety analysis of ocrelizumab in multiple sclerosis. Issue 12 (14th November 2019) - Young, Carolyn; Hauser, Stephen; Kappos, Ludwig; Montalban, Xavier; Hughes, Richard; Koendgen, Harold; McNamara, John; Pradhan, Ashish; Wormser, David; Wolinsky, Jerry
Abstract : Background: Ongoing safety reporting is crucial to understanding the long-term benefit–risk profile of ocrelizumab in patients with multiple sclerosis (MS). The safety/efficacy of ocrelizumab have been characterised in Phase II (NCT00676715 ) and Phase III (NCT01247324 ; NCT01412333 ; NCT01194570 ) trials in patients with relapsing-remitting MS, relapsing MS (RMS) and primary progressive MS (PPMS). We report ongoing safety evaluations from ocrelizumab clinical trials and open-label extension periods up to February 2018. Methods: Safety outcomes were reported for the ocrelizumab all-exposure population in Phase II/III and ongoing Phase IIIb MS trials. The number of post-marketing ocrelizumab-treated patients is based on estimated number of vials sold and US claims data. To account for different exposure lengths, rates per 100 patient years (PY) are presented. Results: In clinical trials, 3, 811 patients with MS received ocrelizumab (10, 919 PY of exposure, as of February 2018). Reported rates per 100 PY (95% confidence interval) were: adverse events (AEs), 242 (239–245); serious AEs, 7.23 (6.73–7.75); infections, 74.5 (72.9–76.1); serious infections, 2.00 (1.74–2.28); and malignancy 0.45 (0.33–0.60). Updated post-marketing data will be presented. Conclusions: Reported rates of events in the ocrelizumab all-exposure population continue to be generally consistent with the controlled treatment period in RMS/PPMS populations. Regular reporting of long-term safety data will continue. Disclosures: Sponsored by F. Hoffmann-La Roche Ltd; writing and editorial assistance was provided by Articulate Science, UK, and funded by F. Hoffmann-La Roche Ltd.